Oxygen Transport Impairments in Miners with Ischemic Stroke-Induced Comas - Yu. A. Churlyaev; A. Z Valiakhmedov; K. V., Lukashev; F. B. Matveyev; R. R. Fatkulin; T. V. Kirsanov (Общая реаниматология)
Objective: to study oxygen transport impairments in ischemic stroke-induced coma in miners who have been doing underground work for more than 10 years. Subjects and methods. A prospective clinical study was conducted in 48 patients with coma caused by ischemic stroke. Group 1 included 12 miners. Group 2 comprised 36 men not working in coal miners. The groups did not differ in age, disease severity, and admission time. However, the group of miners had a higher incidence of pulmonary complications and therefore higher mortality rates. Comprehensive examination was performed and oxygen delivery index (DO2I), oxygen consumption index (VO2I), oxygen extraction ratio, and arteriovenous oxygen difference were calculated in all those admitted to hospital. Results. In ischemic stroke-induced comas, vasoconstriction resulted in the development of circulatory hypoxia with low DO2I. Then on day 3 respiratory and tissue hypoxia developed in the group of those who had a length of underground service. The relationship between DO2I and VO2I found in the miners suggests that impaired lung oxygenizing function was concurrent with oxygen transport system tension. The fact that there was no significant relationship of the oxygen saturation of hemoglobin in venous blood to VO2I in the miners had a high probability of indicating the development of tissue hypoxia. Such relationships were absent in the patients without underground length of service. Conclusion. The miners with an underground service length of 10 years or more and ischemic stroke-induced comas were found to have rapidly developing, more marked and long-term impairments of central hemodynamics, pulmonary oxygenizing function and hence the oxygen transport system as compared to those with no length of underground service. All the above characteristics are due to the lowered reserve capacities of the cardiovascular irnd respiratory systems upon long-term exposure to poor working conditions. Key words: ischemic stroke, oxygen transport, length of underground service, miner.